Urban development in the People’s Republic of China — Closed and open phases of urbanisation - Taubmann, Wolfgang (Raumforschung und Raumordnung | Spatial Research and Planning, 1999)
The traditional Chinese city was considered by the Chinese Communist Party to be the very embodiment of the feudal system; “consumer cities” were, therefore, to be transformed into “producer cities”. However, at a time when the prime focus was on building up Chinese industry, this slogan was less the aim of a new urbanisation strategy than a matter of the cities being seen as low-cost locations for industrial development. Even though living conditions in the cities were impoverished, urbanisation nonetheless repeatedly unleashed waves of migration from the countryside into the cities. Chinese society was split into a rural population and an urban population. Only with the economic reforms of the late ’70s did these structures slowly begin to dissolve.
Keywords: Article